When Modern Little Red Riding Hoods Cross Borders… or Don’t… - Beckett, Sandra (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractMany contemporary retellings of Little Red Riding Hood, the best-known of all fairy tales, are by major, award-winning authors and illustrators, but all too often they remain completely unknown in the anglophone world. This paper examines retellings from numerous countries to show why or why not they cross international borders.